THE TEXT OF PLINY, HN 19.4–5. (May 2020) - Jacobs, John
Abstract : In the passage about the flax plant, lini natura et miracula ( HN 1.19) at the beginning of Book 19 (1–25) of his Naturalis historia, Pliny launches into a moralizing diatribe on man's assault against Nature, fulminating against the evils which man brings upon himself by taking to the high seas in ships with sails. The passage culminates in the rhetorical outburst audax uita, scelerumque plena (19.4), which serves as something of a moral aphorism for the jeremiad as a whole. Although it has been the subject of much discussion in Plinian scholarship, the text still remains in need of attention ( HN 19.4–5): audax uita, scelerumque plena! aliquid seri, ut uentos procellasque capiat, 5. et parum esse fluctibus solis uehi, iam uero nec uela satis esse maiora nauigiis, sed, cum uix amplitudini antemnarum singulae arbores sufficiant, super eas tamen addi alia uela, praeterque alia in proris et alia in puppibus pandi, ac tot modis prouocari mortem, denique tam paruo semine nasci quod orbem terrarum ultro citro portet, tam gracili auena, tam non alte a tellure tolli, neque id uiribus suis necti, sed fractum tunsumque et in mollitiem lanae coactum iniuria ad summam audaciam peruenire !